Aerodynamic efficiency study of 2D airfoils and 3D rectangular wing in heavy rain via two-phase flow approach. (June 2014) - Ismail, M; Yihua, Cao; Bakar, Abu; Wu, Zhenlong
Heavy rainfall greatly affects the aerodynamic performance of the aircraft. Aerodynamic efficiency degradation due to the heavy rain has been the cause of many aircraft accidents. We have studied the effects of heavy rain on the aerodynamic efficiency of NACA 0012 2D airfoil cruise and landing configurations and NACA 0012 3D rectangular wing. Our results show significant increase in drag and decrease in lift in heavy rain environment. For our study we used preprocessing software gridgen for creation of geometry and mesh and fluent as solver. Discrete phase modeling has been used to model the rain particles using two-phase flow approach. The rain particles have been assumed to be inert. In simulated rain environment, both the 2D airfoil and 3D wing showed significant decrease in lift and increase in drag. This study will be quite useful for the designer of the commercial aircrafts and unmanned aerial vehicles and will be helpful for training of the pilots to control the airplanes better in heavy rain environment.